Identifikasi Kualitas Batugamping Berdasarkan Analisis Geokimia dan Petrografi Daerah Pilolodaa Provinsi Gorontalo - Paputungan, Ulfanna; Permana, Aang Panji; Akase, Noviar (Journal of Applied Geoscience and Engineering, 2025)
Gorontalo is one of the provinces with significant limestone potential, particularly in the industrial sector. This study aims to identify the quality of limestone found in the Pilolodaa area and its surroundings. The methods used in this research include petrography to determine the limestone facies and XRF analysis to identify the mineral composition of the rocks. The study area consists of lithologies such as floatstone limestone facies, carbonate sandstone, and alluvial units. The floatstone limestone has a CaO composition greater than 50% and MgO less than 2%, making it highly potential for industrial applications.